Alkyl chain modified zeolite doped polydimethylsiloxane mixed matrix membrane as well as preparation method and application thereof
By grafting the alkyl chains on the MFI zeolite and doping them into polydimethylsiloxane, a mixed matrix membrane for separation of dimethyl carbonate and methanol azeotropic mixture was prepared, which solved the problems of high energy consumption and high equipment cost in the prior art, and achieved excellent adsorption and diffusion of DMC molecules, improving the permeability flux and separation factor.
Patent Information
- Application Number
- CN202411746792.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-02
AI Technical Summary
The prior art has problems of high energy consumption and high equipment cost when separating azeotropic mixtures of dimethyl carbonate and methanol, and the design and customization of DMC selective films face challenges, especially in preferential penetration of DMC over methanol.
A mixed matrix membrane was prepared by grafting alkyl chains of different carbon numbers on the MFI zeolite to form an alkyl chain modified zeolite and doping it into polydimethylsiloxane. The membrane provides an adjustable transport channel for organic molecules, enhancing preferential adsorption and diffusion of DMC molecules.
When separating the azeotropic mixture of dimethyl carbonate and methanol, the mixed matrix membrane significantly enhances the affinity for DMC molecules, reduces the transmission resistance of DMC through the membrane, and exhibits excellent permeability flux and separation factors.
Smart Images

Figure CN119701691A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an alkyl chain modified zeolite doped polydimethylsiloxane mixed matrix membrane and a preparation method and application thereof, belonging to the technical field of membrane separation. Background Art
[0002] The effective separation of organic-organic azeotropic mixtures is crucial for industries such as pesticides, petrochemicals, and pharmaceuticals. Dimethyl carbonate (DMC) is a green chemical product that has attracted much attention in recent years. It can be used for carbonylation and methylation reactions, and the crude product obtained is a DMC-methanol (MeOH) azeotropic mixture. The current technologies for separating DMC-methanol azeotropic mixtures, such as azeotropic distillation, pressure swing distillation, and low-temperature crystallization, have the disadvantages of high energy consumption and high equipment cost. In contrast, pervaporation membrane technology shows great potential in separating DMC-methanol azeotropic mixtures due to its clean, energy-saving and high efficiency. Membranes used for DMC-methanol separation can be divided into two categories: methanol selective membranes and DMC selective membranes. From the perspective of energy consumption, pervaporation is more suitable for preferentially removing a small amount of components in the mixture because the latent heat of vaporization of methanol is much higher than that of DMC (1073.6 vs 381.4 KJ / mol). Therefore, DMC selective membranes are more advantageous in practical industrial applications.
[0003] Polydimethylsiloxane (PDMS), a commercial membrane material, is one of the most studied DMC selective membranes. Improving the permeation flux of the membrane is an effective way to improve the processing capacity of raw materials in the separation process. The separation layer affects the permeation flux of the composite membrane. Thinner membrane layers can achieve higher fluxes, but are also more prone to aggregates and structural defects in the polymer chains, which can reduce the durability and separation factor of the membrane. Another promising approach is to incorporate microporous fillers into polymers to form mixed matrix membranes (MMMs). However, research on MMMs for improving the selective permeation performance of DMC is still limited. The potential of effective fillers for developing DMC permeable membranes remains to be explored. Compared with the widely studied methanol selective membranes, the design and customization of DMC selective membrane materials face more challenges in the following two aspects: (i) there are fewer polymers and inorganic fillers that preferentially permeate DMC rather than methanol; and (ii) the molecular dynamic diameter of DMC is larger than that of methanol, resulting in lower diffusion selectivity through the membrane. Summary of the invention
[0004] The purpose of the present invention is to provide an alkyl chain modified zeolite doped polydimethylsiloxane mixed matrix membrane and its preparation method and application, by grafting alkyl chains with different carbon numbers on MFI type zeolite, providing adjustable transmission channels for organic molecules, so as to capture organic molecules into zeolite pores, enhance the preferential adsorption of organic molecules and subsequent diffusion through zeolite pores. When separating dimethyl carbonate / methanol azeotropic mixture, the mixed matrix membrane enhances the affinity for DMC molecules, reduces the transmission resistance of DMC through the membrane, and exhibits excellent permeation flux.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is:
[0006] An alkyl chain modified zeolite doped polydimethylsiloxane mixed matrix membrane, the mixed matrix membrane comprises a polydimethylsiloxane matrix doped with an MFI type zeolite, and the MFI type zeolite is grafted with carbon numbers of C1-C 16 of the alkyl chain.
[0007] The method for preparing the above-mentioned alkyl chain modified zeolite doped polydimethylsiloxane mixed matrix membrane comprises the following steps:
[0008] S1, preparing MFI zeolite, then dispersing the MFI zeolite into a solution containing a silane coupling agent, heating the solution for reaction, centrifuging, washing, and drying the solution to obtain an alkyl chain modified zeolite;
[0009] S2, dispersing the alkyl chain modified zeolite and the cross-linking agent into the polydimethylsiloxane solution to prepare the casting solution, and drying after the membrane is formed to obtain the mixed matrix membrane.
[0010] Preferably, in step S1, the preparation method of MFI zeolite is to disperse tetraethoxysilane in an aqueous solution of tetrapropylammonium hydroxide to obtain a gel, and then discard the supernatant after heating, and then centrifuge, wash, calcine and grind.
[0011] Preferably, the molar ratio of tetraethoxysilane, tetrapropylammonium hydroxide and water is (2-7):(90-105):(200-300).
[0012] Preferably, the heating conditions are: 150-180°C, 48-96h;
[0013] The calcination conditions are: 500-650°C, 8-24h.
[0014] Preferably, in step S1, the ratio of MFI zeolite to silane coupling agent is (1-5) g: (1-3) mmol; wherein,
[0015] The silane coupling agent is any one of methyltriethoxysilane, isobutyltriethoxysilane and octyltriethoxysilane.
[0016] Preferably, in step S1, the heating reaction conditions are: 90-120° C., 20-48 h;
[0017] The drying conditions are: 100-150℃.
[0018] Preferably, in step S2, the concentration of the polydimethylsiloxane solution is 3-10wt%;
[0019] The amount of the alkyl chain modified zeolite added is 5-65% of the total mass of the alkyl chain modified zeolite and the polydimethylsiloxane;
[0020] The mass ratio of the crosslinking agent to polydimethylsiloxane is 1:(8-15).
[0021] Preferably, in step S2, a coating method is used to form the film, and after the film is formed, it is exposed to air for 1-5 hours and then dried at 60-100° C. for 12-40 hours.
[0022] Application of the above-mentioned alkyl chain modified zeolite doped polydimethylsiloxane mixed matrix membrane in separation of dimethyl carbonate and methanol.
[0023] The beneficial effects of the present invention are:
[0024] Mixed matrix membranes were prepared by incorporating zeolites with adjustable pore chemistry (alkyl chains with different carbon numbers (C1, C4, C8) grafted onto MFI zeolites) into the benchmark membrane material polydimethylsiloxane (PDMS), thereby providing adjustable transport channels for organic molecules. The organophilic alkyl chains can capture organic molecules into the zeolite pores, but due to the steric hindrance effect, they can also hinder the diffusion of organic molecules through the zeolite, which is beneficial to the effective separation of dimethyl carbonate / methanol azeotropic mixtures, and exhibits excellent permeation flux when separating dimethyl carbonate / methanol azeotropic mixtures. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 Schematic diagram of adjusting the pore chemistry of MFI zeolite fillers in polydimethylsiloxane (PDMS) membranes to achieve selective transport of DMC and methanol molecules;
[0026] Figure 2 Scanning electron microscopy (SEM) images of (a) pristine Si-MFI and MFI with tunable pore chemistry (b: MTES-MFI, c: IBTES-MFI, d: OTES-MFI);
[0027] Figure 3 (a) X-ray diffraction (XRD) spectra of Si-MFI and functionalized MFI (MTES-MFI, IBTES-MFI, OTES-MFI), (b) Fourier transform infrared (FTIR) spectra;
[0028] Figure 4 (a) Nitrogen adsorption curve, (b) BET specific surface area of Si-MFI and functionalized MFI (MTES-MFI, IBTES-MFI and OTES-MFI);
[0029] Figure 5 Scanning electron microscopy (SEM) images of (ae) surfaces and (fj) cross sections of (a, f) polydimethylsiloxane (PDMS) membranes, 30 wt% Si-MFI / PDMS membranes (b, g), and 30 wt% functionalized MFI / PDMS mixed matrix membranes (MMMs) ((c, h) MTES-MFI, (d, i) IBTES-MFI, (e, j) OTES-MFI);
[0030] Figure 6 (a) X-ray diffraction (XRD) spectra and (b) attenuated total reflectance Fourier transform infrared (ATR-FTIR) spectra of pure PDMS film and four MFI / PDMS mixed matrix membranes (MMMs);
[0031] Figure 7 Adsorption curves of (a) pure polydimethylsiloxane (PDMS) membrane, (b) MTES-MFI / PDMS, (c) IBTES-MFI / PDMS and (d) OTES-MFI / PDMS mixed matrix membranes (MMMs) in dimethyl carbonate (DMC) and methanol;
[0032] Figure 8 Low-frequency nuclear magnetic resonance (LF-NMR) signals of PDMS membrane, Si-MFI / PDMS MMMs and MTES-MFI / PDMS MMMs in (a) methanol and (b) dimethyl carbonate (DMC);
[0033] Fig. 9 Pervaporation performance of (a) pure PDMS membrane, PDMS MMMs containing four MFI fillers with a loading of 30 wt%, and (b) MTES-MFI / PDMS MMMs with different loadings (operating conditions: 30 wt% DMC / methanol, 40 °C);
[0034] Fig.10 Surface and cross-sectional SEM images of MTES-MFI / PDMS MMMs with different loading amounts (a, d: 10 wt%; b, e: 30 wt%; c, f: 50 wt%);
[0035] Fig.11Pervaporation performance of MTES-MFI / PDMS MMMs at different feed DMC concentrations (operating temperature: 40 °C): (a) permeate flux; (b) separation factor and DMC content in the permeate;
[0036] Fig.12 Pervaporation performance of 50 wt % MTES-MFI / PDMS MMM at different operating temperatures (feed concentration: 30 wt % DMC / methanol): (a) permeation flux and separation factor; (b) Arrhenius plot;
[0037] Fig.13 Long-term pervaporation performance of 50 wt % MTES-MFI / PDMS MMM for separation of 30 wt % DMC / methanol at 40 °C. DETAILED DESCRIPTION
[0038] In this example, a novel mixed matrix membrane for separation of azeotropic mixtures was constructed by incorporating MFI zeolite with tunable pore chemistry into a PDMS matrix. Figure 1 As shown, MFI zeolite provides adjustable transport channels for organic molecules by grafting alkyl chains with different carbon numbers (C1, C4, C8). The purpose of designing organophilic alkyl chains is to capture organic molecules into zeolite pores to enhance the preferential adsorption of organic molecules and subsequent diffusion through the zeolite pores. At the same time, the steric hindrance effect of the grafted alkyl chains on the entry and diffusion of organic molecules was explored. Through a combination of systematic characterization and pervaporation process, the key role of zeolite pore chemistry on the physicochemical properties, molecular transport properties and DMC-methanol separation performance of alkyl-grafted MFI / PDMS mixed matrix membranes was revealed.
[0039] raw material
[0040] Vinyl-terminated polydimethylsiloxane (PDMS, RTV 615, Huazhisheng, Shenzhen), polytetrafluoroethylene (PTFE, average pore size: 100 nm, Beijing Haicheng Shijie), dimethyl carbonate (DMC, MacLean), deionized water (Wahaha, Hangzhou). Methanol, n-heptane, tetraethoxysilane (TEOS), tetrapropylammonium hydroxide (TPAOH, 25% aqueous solution) were purchased from China National Pharmaceutical Chemical Reagent Co., Ltd. Methyltriethoxysilane (MTES), isobutyltriethoxysilane (IBTES) and octyltriethoxysilane (OTES) were purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. All solvents were not further purified.
[0041] Synthesis of zeolite fillers with tunable pore chemistry
[0042] For a typical MFI zeolite synthesis, a certain amount of TPAOH is poured directly into deionized water. When the mixed solution is clarified (solution A), TEOS is added dropwise to solution A. After stirring at a speed of about 800 rpm for about 6 hours, a uniform gel with a molar ratio of 5.0TEOS:96TPAOH:250H2O is finally formed, which is transferred to a hydrothermal autoclave and placed in a high-temperature oven preheated at 160°C for 72 hours. After the reaction is completed, the supernatant is poured off, and the solid particles are washed several times with deionized water by centrifugation, and then transferred to a muffle furnace and calcined at 550°C for at least 8 hours to remove the organic template from the pores. Finally, a white powder is obtained by mechanical grinding for alkylation modification and preparation of mixed matrix membranes (MMMs).
[0043] The MFI particles were functionalized to obtain adjustable pore chemistry in the following manner: 2 mmol of silane coupling agent (MTES, IBTES or OTES) was first mixed with 15 g of n-heptane solution, and then 2 g of the MFI zeolite powder prepared above was dispersed into the mixed solution and fully stirred and refluxed in an oil bath at 100°C overnight. After centrifugation, the functionalized particles were washed three times with n-heptane, and then the remaining solvent was removed in a vacuum oven at 120°C. The obtained MFI samples with adjustable pore chemistry were named MTES-MFI, IBTES-MFI and OTES-MFI, respectively.
[0044] Membrane preparation
[0045] A certain amount of PDMS monomer was uniformly dispersed in 15 ml of n-heptane solution to prepare a 5 wt% PDMS solution. MFI / (M MFI +M PDMS ), wt %) of MFI or functionalized MFI particles were poured into the above PDMS solution, ultrasonically treated and stirred for 1 h to form a uniform suspension. Subsequently, a crosslinker (the mass ratio of monomer to crosslinker was 10:1) was added to ensure sufficient crosslinking. The solution with appropriate viscosity was coated on the PTFE substrate by a doctor blade coating method. Finally, the fresh MMM was exposed to air for 2 h and then transferred to an oven at 80 ° C for more than 12 h to obtain the original MFI / PDMS and functionalized MFI / PDMS MMMs.
[0046] Characterization
[0047] The structure and morphology of the MMMs were analyzed using a field emission scanning electron microscope (Phenom Pharos G2, The Netherlands) at 10 kV. The crystal structure of the films was determined using X-ray diffraction (XRD, Miniflex 600, Rigaku, Japan) in the 2θ range of 5°-50° and a scanning speed of 20° / min. Fourier transform infrared spectroscopy (ATR-FTIR, PerkinElmer, USA) was used to analyze the structure and morphology of the MMMs at 10 kV. -1 The chemical functional groups of the films and powders were analyzed in the wavelength range of 1000 nm. The N2 isotherms were measured at 77 K using a fully automatic Brunner-Emmett-Teller (BELSOR-MAX, Microtrac-BEL, Japan) adsorption apparatus to calculate the surface area of the filler. The T2 inversion spectra of the films were measured using low-field nuclear magnetic resonance spectroscopy (LF-NMR, Bruker minispec MQ60, Germany).
[0048] The solubility and diffusion coefficient of DMC and methanol in the membrane without PTFE substrate were measured by gravimetric method. The size and shape of the membrane samples were the same for more accurate comparison. The membranes were immersed in pure methanol and pure DMC solvents at a constant temperature (25°C). After a period of time, the residual organic solvent on the surface of the membrane sample was quickly wiped off with dust-free paper. When the weight of the membrane sample no longer increased, it indicated that the solvent absorption of the membrane sample had reached equilibrium.
[0049] Separation of DMC-Methanol Mixture by Pervaporation
[0050] This experiment used a pervaporation device with an effective membrane area of 4.9 cm 2 . The raw organic mixture was transported by a peristaltic pump and circulated on the membrane surface. The downstream side of the membrane was evacuated by a vacuum pump, and the downstream pressure was maintained below 200 Pa. The DMC concentrations on the raw and permeate sides were measured using a gas chromatograph (Agilent 8860GC, USA). The results for each membrane sample were measured at least three times. The separation factor (β), permeate flux (J) and normalized flux (J') (normalized membrane thickness was 8 μm) were calculated as follows:
[0051] J=M / At,
[0052]
[0053] M represents the total weight of the permeate collected during the operation time, in kg; t represents the operation time of the pervaporation process, in h; A is the effective membrane area, in m 2 ; l is the thickness of the membrane in μm; in addition, x and y represent the mass fractions of DMC (D) or methanol (M) in the feed side and the permeate side, respectively.
[0054] Properties of functionalized MFI and MFI particles
[0055] Silanes with different alkyl chain lengths were selected to tune the pore chemistry of the MFI zeolite filler. The morphology of the original Si-MFI and MFI particles with tunable pore chemistry is shown in Figure 2. Figure 2 The average particle size of these particles is about 500 nm.
[0056] The crystal structure of MFI particles with tunable pore chemistry was investigated by X-ray diffraction (XRD), e.g. Figure 3 The diffraction peaks in the range of 5° to 50° confirm that the synthesized MFI powder has a good crystal structure and the functionalized MFI particles still maintain their crystal structure. The chemical properties of the MFI powder were measured using Fourier transform infrared spectroscopy (FTIR). Figure 3 As shown in the middle b area, 1081cm -1 The absorption peak at 2965 cm-1 is attributed to the stretching vibration of the Si-O-Si main chain. -1 and 2856cm -1 The absorption peaks at , were identified as the stretching vibrations of -CH3 and -CH2- groups, respectively. The study found that with the increase of the carbon number of the alkyl chain on the functionalized MFI particles, the peak intensity of -CH3 and -CH2- groups increased compared with the original MFI, indicating that the pore chemistry of the MFI particles has been successfully regulated by the silane coupling agent.
[0057] like Figure 4 As shown in region a, the nitrogen adsorption curves of the four powders in the relative pressure range of 0-1.0 exhibit a type I isotherm, suggesting a microporous crystalline structure. It was observed that when the pore chemistry of the MFI powders was adjusted using silane coupling agents with alkyl chains of different lengths, the nitrogen adsorption of the functionalized MFI powders showed a decreasing trend compared to the original MFI powders, which was attributed to the alkyl chains occupying the pore structure of the MFI. The BET surface area measurements of the four MFI powders are shown in Figure 2. Figure 4 As shown in area b, the longer the silane chain of MFI functionalization, the lower the BET surface area, which is due to the reduction of adsorption sites and pore volume.
[0058] Characteristics of mixed matrix membranes
[0059] Pristine polydimethylsiloxane (PDMS) membranes and PDMS mixed matrix membranes (MMMs) containing four different MFI fillers were prepared, and the filler loading was 30 wt %. The surface and cross-sectional morphologies of pure PDMS membranes, Si-MFI / PDMS membranes, and functionalized MFI / PDMS membranes (coated on polytetrafluoroethylene (PTFE) substrates) are shown in Figure 2 . Figure 5 As shown. In all membranes, the dense separation layer exhibited good interfacial adhesion with the porous PTFE layer. The thickness of the separation layer was about 8 μm. In addition, it was observed that Si-MFI and alkyl chain functionalized MFI particles were uniformly dispersed in the cross-linked PDMS layer.
[0060] like Figure 6 As shown in Figure 2, the physicochemical properties of the PDMS-based membranes were characterized and measured by X-ray diffraction (XRD) and attenuated total reflectance Fourier transform infrared spectroscopy (ATR-FTIR). The pure PDMS membrane exhibits a broad peak at about 12°, indicating that the PDMS polymer is an amorphous structure. When Si-MFI and functionalized MFI are incorporated into the PDMS membrane, the characteristic peaks of MFI appear, which means that the crystal structure of MFI is preserved. The FTIR spectra of PDMS and MMMs are shown in Figure 2. Figure 6 Shown in area b. 1097cm -1 、800cm -1 and 1262cm -1 The peaks at 2963cm represent the deformation vibration of Si-O-Si main chain and Si-C bond respectively. -1 The peak at represents the asymmetric CH stretching vibration of the CH3 group in the side chain.
[0061] Adsorption testing and low-frequency nuclear magnetic resonance (LF-NMR) characterization of membranes
[0062] The adsorption capacity of the membrane sample is determined by measuring its mass change after immersion in different solvents, and its affinity for the solvent can be evaluated. Figure 7 As shown, the adsorption curves of functionalized PDMS MMMs and PDMS membranes in methanol and dimethyl carbonate (DMC) solvents were compared. It was observed that the adsorption curves of all mentioned membranes for DMC greatly exceeded that for methanol, indicating that the hydrophobic PDMS-based membranes have a significant affinity for the non-polar DMC molecules. Specifically, as can be seen from Table 1, MTES-MFI / PDMS MMMs have the largest adsorption of DMC, and the order of membrane adsorption of DMC is: MTES-MFI / PDMS>PDMS>IBTES-MFI or OTES-MFI / PDMS. MTES-MFI / PDMS MMMs also showed a slight increase in the adsorption of methanol. The enhancement of MTES-MFI / PDMS MMMs for DMC is much greater than that for methanol, which confirms that MTES-MFI fillers preferentially adsorb DMC rather than methanol. However, the longer alkyl chains (C4 or C8) in IBTES or OTES partially blocked the pore structure of the MFI filler, resulting in a decrease in the adsorption amount in PDMS MMMs compared to that of pure PDMS membranes.
[0063] Table 1 According to Figure 7 Calculated adsorption results for different membranes
[0064]
[0065] To further study the adsorption behavior of PDMS-based membranes in organic solvents, the transverse relaxation time T2 distribution was analyzed using low-frequency nuclear magnetic resonance (LF-NMR) technology. The hydrogen protons in the membrane or solvent are represented by the relative intensity of the T2 signal peak. The T2 relaxation times of the three membranes in DMC or methanol solvents were studied. Figure 8 As shown, high T 2l The signal peak position (1000-10000ms) corresponds to the free solvent molecules. 2a The signal peak (less than 1000ms) is the 1H signal peak of the solvent molecules adsorbed in the membrane pores or on the membrane surface. In PDMS membrane, Si-MFI / PDMS and MTES-MFI / PDMS MMMs, it was found that in DMC solvent, the T 2a Signal peak intensity accounts for the total intensity (T 2a +T 2l ) percentage was significantly higher than that of the other two membranes, and the affinity of MTES-MFI / PDMS MMM to DMC was stronger than that to methanol.
[0066] Pervaporation performance
[0067] To further understand the effect of functionalized MFI / PDMS MMMs on the pervaporation performance, they were compared with pristine MFI / PDMS and pure PDMS membranes. Fig. 9 As shown in region a, under the same test conditions, the thickness-normalized flux of the functionalized MFI / PDMSMMMs is higher than that of the pure PDMS membrane. This result indicates that the addition of the MFI filler functionalized with non-polar alkyl chains promotes the preferential adsorption of non-polar DMC molecules on the membrane surface. In contrast, the separation performance of the original MFI / PDMS MMMs is lower than that of the pure PDMS membrane. This is due to the presence of residual hydroxyl groups on the surface and in the pores of the MFI particles. As the number of carbon atoms in the functionalized alkyl chain increases, the permeation flux and separation factor show a downward trend. This phenomenon is due to the fact that longer alkyl chains reduce the intrinsic pore size and hinder the passage of organic molecules (especially DMC) through the MFI filler due to steric hindrance.
[0068] The effect of MTES-MFI loading on membrane performance was further studied. Fig. 9 As shown in the middle b area. It can be seen that with the increase of MTES-MFI loading, the flux gradually increases and the separation factor is also enhanced. The thickness normalized flux and separation factor of 50wt% MTES-MFI / PDMSMMM are 14.0kg / m2 h and 3.6, which are 1.8 and 1.1 times that of pure PDMS membrane, respectively. On the one hand, 50wt% loading of MTES-MFI filler can provide relatively continuous diffusion channels in MMMs because the dispersed fillers are tightly connected and defect-free in the PDMS matrix, thereby reducing the transmission resistance of the MTES-MFI / PDMS membrane layer. On the other hand, the affinity of MTES-MFI / PDMS MMMs for DMC molecules is stronger than that for methanol molecules, which can improve the separation factor.
[0069] In addition, the surface and cross-sectional morphologies of MTES-MFI / PDMSMMMs with loadings of 10-50 wt% were observed by scanning electron microscopy (SEM). Fig.10 ). As the MTES-MFI filler loading increases, the particles are evenly dispersed in the membrane layer without agglomeration, and the membrane surface becomes rough. In addition, no pinholes appear on the surface and cross-section of the 50wt% MTES-MFI / PDMS MMM, indicating that even with a filler loading of up to 50wt%, there is still good interfacial compatibility between the functionalized MFI filler and the polymer matrix.
[0070] The separation performance under several key operating conditions (such as feed concentration, operating temperature, and long-term measurement) was systematically studied to explore the feasibility of the practical application of 50wt% MTES-MFI / PDMS MMM. Fig.11 As shown in Figure 2, the permeate flux, separation factor, and DMC concentration in the permeate all vary linearly with the change of DMC concentration from 10 wt% to 50 wt%. Since the membrane has a stronger affinity for the DMC solvent, a higher DMC feed concentration will swell the polymer matrix and increase the free volume of the polymer network, which helps to promote the diffusion process.
[0071] Fig.12 The effect of feed temperature on the pervaporation performance of 50wt% MTES-MFI / PDMS MMMs is shown. Fig.12 As shown in area a, as the operating temperature increases, the permeation flux increases, while the separation factor is the opposite. On the one hand, as the feed temperature increases, the pressure difference of the feed components and the migration of the polymer chains increase simultaneously, resulting in a decrease in the transmission resistance and promoting the diffusion of the permeating molecules through the membrane layer. On the other hand, since the molecular dynamics diameter of methanol is smaller than that of DMC, when the operating temperature increases, the methanol flux increases faster than the DMC flux, resulting in a slight decrease in the separation factor. The dependence of the DMC flux and the methanol flux on temperature was further studied using the Arrhenius equation. Activation energy (E a ), the higher the component flux is, the more sensitive it is to the operating temperature. Fig.12As shown in region b, for 50 wt% MTES-MFI / PDMS MMM, the E of DMC between 30 °C and 60 °C a The value is lower than that of methanol a This indicates that the partial flux of methanol during pervaporation is more sensitive to the operating temperature.
[0072] like Fig.13 As shown in Figure 2, the long-term separation performance of 50wt% MTES-MFI / PDMS membrane for 30wt% DMC / methanol azeotropic mixture at 40°C was studied. Within 150h of continuous operation, 50wt% MTES-MFI / PDMS MMM exhibited stable permeation flux and separation factor. Overall, PDMS MMM has high permeation flux and good stability, and has great potential in practical applications in the separation of organic azeotropes.
[0073] Comparison of separation performance with literature
[0074] In the past two decades, there have been many reports on the use of PDMS-based mixed matrix membranes (MMMs) for the pervaporation process of separating DMC / methanol azeotropes, which are listed in Table 2. It was demonstrated that the alkylated modified microporous zeolites have a stronger affinity for DMC than for methanol and provide fast transport channels for DMC. In this application, the optimal MTES-MFI / PDMS MMMs with loadings up to 50 wt% exceeded the performance of the current state-of-the-art membranes for DMC / methanol separations.
[0075] Table 2 Comparison of pervaporation performance of PDMS-based mixed matrix membranes for separation of DMC / methanol azeotropic mixtures
[0076]
[0077] Reference 1: L. Wang, X. Han, J. Li, L. Qin, D. Zheng, Preparation of modified mesoporous MCM-41 silica spheres and its application in pervaporation, Powder Technol. 231 (2012) 63-69. Reference 2: Z. Liu, W. Lin, Q. Li, Q. Rong, H. Zu, M. Sang, Separation of dimethyl carbonate / methanol azeotropic mixture by pervaporation with dealcoholized room temperature-vulcanized silicone rubber / nanosilica hybrid active layer, Sep. Purif. Technol. 248 (2020) 116926.
[0078] Reference 3: L. Wang, X. Han, J. Li, D. Zheng, L. Qin, Modified MCM-41 silica spheres filled polydimethylsiloxane membrane for dimethyl carbonate / methanol separation via pervaporation, J. Appl. Polym. Sci. 127(6) (2013) 4662-4671.
[0079] Reference 4: L. Wang, X. Han, J. Li, X. Zhan, J. Chen, Hydrophobic nano-silica / polydimethylsiloxane membrane for dimethyl carbonate-methanol separation via pervaporation, Chem. Eng. J. 171(3) (2011) 1035-1044.
[0080] In summary, this application proposes a strategy to enhance the azeotropic separation performance of polydimethylsiloxane (PDMS) membranes by adjusting the chemical properties of the filler pores. Compared with the performance of long alkyl chain functionalized MFI (C4 or C8) / PDMS mixed matrix membranes (MMMs), the short alkyl chain (C1) functionalized MFI filler at a loading of 50wt% not only enhances the membrane's affinity for dimethyl carbonate (DMC) relative to methanol, but also reduces the transport resistance of DMC through the membrane. Therefore, 50wt% MTES-MFI / PDMS MMMs exhibited a separation efficiency of 11.5kg / m when separating a 30wt% DMC / methanol azeotropic mixture at 40°C. 2 h permeation flux and a separation factor of 3.6, showing great potential for practical applications.
[0081] The above is only a preferred implementation of the patent of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the patent of the present invention. These improvements and modifications should also be regarded as the scope of protection of the patent of the present invention.
Claims
1. An alkyl chain modified zeolite doped polydimethylsiloxane mixed matrix membrane, characterized in that: The mixed matrix membrane comprises a polydimethylsiloxane matrix doped with an MFI type zeolite, and a carbon number of C1-C 16 of the alkyl chain.
2. The method for preparing the alkyl chain modified zeolite doped polydimethylsiloxane mixed matrix membrane according to claim 1, characterized in that: The steps include: S1, preparing MFI zeolite, then dispersing the MFI zeolite into a solution containing a silane coupling agent, heating the solution for reaction, centrifuging, washing, and drying the solution to obtain an alkyl chain modified zeolite; S2, dispersing the alkyl chain modified zeolite and the cross-linking agent into the polydimethylsiloxane solution to prepare the casting solution, and drying after the membrane is formed to obtain the mixed matrix membrane.
3. The method for preparing the alkyl chain modified zeolite doped polydimethylsiloxane mixed matrix membrane according to claim 2, characterized in that: In step S1, the preparation method of MFI zeolite is to disperse tetraethoxysilane in an aqueous solution of tetrapropylammonium hydroxide to obtain a gel, discard the supernatant after heating, and then centrifuge, wash, calcine and grind.
4. The method for preparing the alkyl chain modified zeolite doped polydimethylsiloxane mixed matrix membrane according to claim 3, characterized in that: The molar ratio of tetraethoxysilane, tetrapropylammonium hydroxide and water is (2-7):(90-105):(200-300).
5. The method for preparing the alkyl chain modified zeolite doped polydimethylsiloxane mixed matrix membrane according to claim 3, characterized in that: Heating conditions are: 150-180°C, 48-96h; The calcination conditions are: 500-650°C, 8-24h.
6. The method for preparing the alkyl chain modified zeolite doped polydimethylsiloxane mixed matrix membrane according to claim 2, characterized in that: In step S1, the ratio of MFI zeolite to silane coupling agent is (1-5) g: (1-3) mmol; wherein the silane coupling agent is any one of methyltriethoxysilane, isobutyltriethoxysilane and octyltriethoxysilane.
7. The method for preparing the alkyl chain modified zeolite doped polydimethylsiloxane mixed matrix membrane according to claim 2, characterized in that: In step S1, the heating reaction conditions are: 90-120° C., 20-48 h; The drying conditions are: 100-150℃.
8. The method for preparing the alkyl chain modified zeolite doped polydimethylsiloxane mixed matrix membrane according to claim 2, characterized in that: In step S2, the concentration of the polydimethylsiloxane solution is 3-10wt%; The amount of the alkyl chain modified zeolite added is 5-65% of the total mass of the alkyl chain modified zeolite and the polydimethylsiloxane; The mass ratio of the crosslinking agent to polydimethylsiloxane is 1:(8-15).
9. The method for preparing the alkyl chain modified zeolite doped polydimethylsiloxane mixed matrix membrane according to claim 2, characterized in that: In step S2, a coating method is used to form a film, and after the film is formed, it is exposed to air for 1-5 hours and then dried at 60-100° C. for 12-40 hours.
10. Use of the alkyl chain modified zeolite doped polydimethylsiloxane mixed matrix membrane according to claim 1 in separation of dimethyl carbonate and methanol.
Citation Information
Patent Citations
Preparation for silicone hydride modified zeolite filled silicon rubber compound film
CN101318111A
Preparation method of pervaporation film with preferential penetration of dimethyl carbonate
CN102350233A
Mixed matrix membrane and preparation method thereof
CN107737535A
Mixed matrix membrane containing oleophobic all-silicon molecular sieve
CN116510530A
Gas separating asymmetric membrane
JP2004267810A